A dimensão educativa no trabalho profissional do assistente social no S.U.A.S.: a realidade de Santos, SP - Luz, Luziene Aparecida da (2015)
This study aims to understand how the educational dimension is captured and held by social workers in their work process in the Single Social Assistance System in the city of Santos, Brazil. Therefore, it is considered that social work is constituted as a registered profession in the social and technical division of collective work, and has the social question the basic foundation of their actions. Also, that every action is education, because education is not present only in the proper space, but is inherent in all social relations. So there is the work of the social worker, the educational dimension as something intrinsic to make professional and that permeates any action or instrumental in the work everyday and this happens in different ways. It is a qualitative research with analysis of interviews of nine social workers in the city of Santos, SP that based on several considerations for the proposed theme